The Influence of Human Dignity Concept in Islamic Sharia Economics: An Integrative Perspective - Bekti, Fitri Indah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study explores the influence of the concept of inherent human dignity in the context of Islamic Sharia economics. In this study, a desk research approach is used to collect data from relevant written sources. The discussion on human dignity will be analyzed through three main perspectives: international human rights instruments, Islamic declarations on human rights, and Islamic references, particularly the Quran. The results show that the concept of human dignity is not only a foundation for human rights, but also has significant implications in the development of Islamic Sharia economics. This study underscores the importance of understanding human dignity in formulating economic principles based on justice and blessings.